A Brand New Applied Higher Education Model Exploration and Informatization of "Zhong Ben Yi Ti Hua" - Junfeng Liu (The International Journal of Multiphysics, 2024)
"Zhong Ben Yi Ti Hua"(ZBYTH) that is an innovative integration of secondary and bachelor education, it refers to a novel educational model that combines three years of secondary vocational education with four years of applied undergraduate education, forming a seamless seven-year program. This paper delves into the development process of the " ZBYTH" project at Zhejiang University of Science and Technology, detailing the specifics of its training system. Based on this analysis, we propose targeted improvement suggestions tailored to practical conditions. We also describe the concrete measures the university adopted through educational informatization, and the outcomes and impacts of these implementations. By thoroughly analyzing this process, the paper aims to provide valuable insights and references for the optimization and enhancement of similar future projects.